2009
DOI: 10.1093/ejo/cjp033
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Streptococcus mutans levels in patients with conventional and self-ligating brackets

Abstract: The objective of this study was to investigate the effect of bracket type (conventional and self-ligating) on the levels of Streptococcus mutans and total bacterial counts in whole saliva of orthodontic patients. Thirty-two male and female patients were selected using the following inclusion criteria: adolescents (mean age 13.6 years, range 11-17 years), fixed appliances in both arches, non-smoker, and no reported oral habits. Demographic and oral hygiene characteristics were determined for each subject. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 20 publications
5
87
0
6
Order By: Relevance
“…However, no significant differences were found between the groups for overall time. In accordance with this, Pandis et al 25 defined no difference in PI between SLBs and CBs with elastomeric ligation. Our result is in contrast with the findings of some researchers 7,8,12,17 who defined that elastomeric ligated CBs cause more plaque accumulation and periodontal inflammation than SLBs.…”
Section: Discussionmentioning
confidence: 74%
“…However, no significant differences were found between the groups for overall time. In accordance with this, Pandis et al 25 defined no difference in PI between SLBs and CBs with elastomeric ligation. Our result is in contrast with the findings of some researchers 7,8,12,17 who defined that elastomeric ligated CBs cause more plaque accumulation and periodontal inflammation than SLBs.…”
Section: Discussionmentioning
confidence: 74%
“…Three studies [43,44,48] detected significant increases of gram-negative bacteria, respectively, at 3 and 6 months, followed by a decrease at 6 and 12 months. Ten studies [10,20,21,26,30,37,41,43,44,48] detected an increase in the percentage of gram-bacteria and A. actinomycetemcomitans . The study conducted by Alves de Souza et al [10] revealed a significant increase in gram-species with the use of elasticomeric rings (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Eigh studies analyzed self-ligating braces (SLB) [9,14,24,3740,54]. Two studies [14,40] revealed no differences for BOP and PI between SLB and CB, while Nalçac et al and Uzuner et al [54] demonstrated a worsening in SLB.…”
Section: Resultsmentioning
confidence: 99%
“…Negative effects on dental hard tissue [10][11][12][13][14][15][16] as well as on the periodontium [1, 7,15,[17][18][19][20][21][22][23][24][25] owing to orthodontic bands and brackets have been described, and several investigations showed that the presence of plaque at the gingival margin is the most important factor in the development of periodontal diseases [18,[26][27][28]. Several reports have highlighted the fact that orthodontic brackets are not only associated with noticeable periodontal adjustments, but that the method of archwire ligation onto fixed braces itself has an apparent influence on bacteria accumulation and periodontal status [2,5,9,29].…”
Section: Introductionmentioning
confidence: 99%
“…According to a number of studies an increase in biofilm accumulation has been reposted in patients with elastomeric ligatures [2,5,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%